Threat to Success Integration and Resettlement for Female Refugee: Exercising Poor Rights to Health - Camelia, A. Indah; Narwati, Enny; Ramadani, R. Yahdi (Faculty of Law, Universitas Brawijaya, 2025)
In the last decade, refugee catastrophe has reached an unprecedented level, with women and children comprising a significant portion of displaced population worldwide. In particular for female refugees, they face unique health challenges, including reproductive health problems, mental health issues, and gender-based violence, despite international law’s recognition of the rights to health as fundamental rights under many international conventions. Female refugee often struggles to access healthcare servicesdue to linguistic and cultural barriers, financial constraints, and discriminatory policy. Limited access to health care affects their ability to secure employment, develop social networks, and actively participate in host communities entail as a threat to theircapability forintegration and resettlement in the new country. The study aimsto examinehow current health policies create barriers to successful integration and resettlementfor female refugees. Then, itproposespolicy recommendations for governments, international organizations, and healthcare providers to address these challenges and promote equitable access to healthcare.This research is a doctrinallegalstudy which investigate the impact of the poor health policy on integration and resettlement prospects for female refugees. This research will start by analysesinternational refugee lawand relevant case law pertaining to healthcare access for refugees. Then, it critically examines the gaps and inconsistencies in these legal frameworks and their impact on the lived experiences of female refugees. Good physical and mental health conditions are key to the refugees' successful integration and resettlement into new societies and labourmarkets; otherwise, securing employment, developing social networks, or becoming active members of their host communities will be challenging. Therefore strategy to address the issue are by improving language services, providing social assistance programs, promoting gender-sensitive approach, and establishing responsive and inclusive health care system.